Common immunity: Biopolitics in the age of the pandemic - Esposito, Roberto; Hanafi, Zakiya (UK Polity press, 2023)
After two years of global pandemic, it is no surprise that immunization is now at the center of our experience. From the medicalization of politics to the disciplining of individuals, from lockdowns to mass vaccination programs, contemporary societies seem to be firmly embedded in a syndrome of immunity. To understand the ambivalent effects of this development, it is necessary to go back to its modern genesis, when the languages of law, politics, and medicine began to merge into the biopolitical regime we have been living under for some time.
Keywords: Political science Philosophy; Medicine political aspects; Immunization Political aspects